Hospitalization and Morbidity Rates After Pediatric Traumatic Brain Injury: A Nation-Wide Population-Based Analysis - Bruns, Nora; Trocchi, Pietro; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian; Stang, Andreas (Frontiers in Pediatrics, 2021)
Background: Even though traumatic brain injury (TBI) is a major cause of morbidity and mortality in children around the globe, population-based and nation-wide data to assess the burden of TBI is scarce. Methods: Based on diagnosis related groups from nation-wide hospital data, we extracted data on all TBI-related hospitalizations in children < 18 years in Germany between 2014 and 2018. We calculated crude, age-specific and standardized incidence rates for hospitalizations, imaging, intracranial injury, neurosurgery, and mortality. Results: Out of 10.2 million hospitalizations, we identified 458,844 cases with TBI as primary or secondary diagnosis, resulting in a crude incidence rate of 687/100,000 child years (CY). Age-specific rates of computed tomography were below 30/100,000 CY until the age of 10 years and increased to 162/100,000 CY until 17 years of age. Intracranial injury was diagnosed in 2.7 %, neurosurgery was performed in 0.7 % of patients, and 0.7 % were mechanically ventilated. Mortality was 0.67/100,000 CY (0.1 %). Conclusions: Despite substantial hospitalization rates for pediatric TBI in Germany, the rates of imaging, the need for mechanical ventilation, neurosurgery and mortality were overall very low. Reasons for hospitalization and measures to reduce unnecessary admissions warrant further investigation.